Relationship Between HbA1c Levels and Atherogenic Index of Plasma in Diabetic Nephropathy Patients - Adithya Nurliza Sitepu; Zulfikar Lubis; Muhammad Aron Pase; Nindia Sugih Arto; Ricke Loesnihari; Almaycano Ginting (Indonesian Journal of Global Health Research, 2026)
Diabetic nephropathy is the leading cause of kidney failure worldwide. Its incidence is comparable to that of cardiovascular disease (CVD), with macrovascular complications remaining the main cause of death among diabetic patients. The Atherogenic Index of Plasma (AIP) is an independent marker and predictor of CVD. AIP indicates risk even when other atherogenic risk factors are normal, categorized as low risk (AIP < 0.11), intermediate risk (AIP 0.11–0.21), and high risk (AIP > 0.21). This study aims to explore the relationship between Glycated Hemoglobin (HbA1c) levels and AIP in patients with diabetic nephropathy to identify the risk of CVD complications. It used a prospective analytical design with a cross-sectional approach, conducted at Adam Malik Hospital, Medan, from February to May 2025. Forty-three outpatients with diabetic nephropathy who met the inclusion criteria were selected using a consecutive sampling technique. Patients were assessed for HbA1c, triglycerides, HDL, and urinary albumin-to-creatinine ratios. AIP was calculated by taking the logarithm of (triglycerides/HDL). Data analysis involved Pearson and Spearman correlation tests. A significant positive correlation was found between HbA1c and AIP (r = 0.670, p = 0.000), as well as between HbA1c and triglycerides (r = 0.398, p = 0.008). A significant negative correlation was observed between HbA1c and HDL (r = -0.648, p = 0.000). However, there was no significant correlation between HbA1c and ACR, nor between ACR and AIP (p > 0.05). In conclusion, higher HbA1c levels are associated with increased AIP levels, which elevate the risk of CVD, characterized by rising triglycerides and decreasing HDL.